Factors Influencing Food Choice in an Australian Aboriginal Community. (March 2014) - Brimblecombe, Julie; Maypilama, Elaine; Colles, Susan; Scarlett, Maria; Dhurrkay, Joanne Garnggulkpuy; Ritchie, Jan; O'Dea, Kerin
We explored with Aboriginal adults living in a remote Australian community the social context of food choice and factors perceived to shape food choice. An ethnographic approach of prolonged community engagement over 3 years was augmented by interviews. Our findings revealed that knowledge, health, and resources supporting food choice were considered "out of balance, " and this imbalance was seen to manifest in a Western-imposed diet lacking variety and overrelying on familiar staples. Participants felt ill-equipped to emulate the traditional pattern of knowledge transfer through passing food-related wisdom to younger generations. The traditional food system was considered key to providing the framework for learning about the contemporary food environment. Practitioners seeking to improve diet and health outcomes for this population should attend to past and present contexts of food in nutrition education, support the educative role of caregivers, address the high cost of food, and support access to traditional foods.